Syntactic Analysis of Ideative Functions in Motorcycle Maintenance Manuals - Yunus, Muhammad; Agung Wicaksono, Bayu; Muntiah Andriami, Sri (EDUPEDIA Publisher, 2024)
This study analyzes the ideative function in the text of motorcycle maintenance manual using functional systemic linguistic approach. The analysis was conducted on 30 sentences in the motorcycle manual to identify processes, participants, and circumstantials. The results show the dominance of material processes that describe real actions, such as remove, check, clean, replace, and install. Frequently mentioned participants are vehicle components, such as body cover, fuel hose, and throttle grip, which are explicitly described to facilitate user understanding. Circumstances provide context of time, manner, and condition, such as with a rag and if it is not in good condition. Instructions serve not only as a guide for action, but also evaluation and corrective measures to maintain vehicle performance. This study concludes that the text of the manual is systematically and effectively designed to help users carry out vehicle maintenance independently and safely.